INFLUENCE OF PRODUCT QUALITY, PRICE AND PROMOTION ON SALES VOLUME OF PATIN NUGGET (Survey at UPR CV. Graha Pratama Fish in Koto Mesjid Village XIII Koto Kampar) - Ahmad, Ghazali; Ali, Auzar; Azhari, Azhari (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of product quality, price and promotion on the sales volume of catfish nuggets at UPR CV. Graha Pratama Fish in Koto Mesjid Village, XIII Koto Kampar District. The population in this study were all consumers who bought catfish nugget products at UPR CV. Graha Pratama Fish in Koto Mesjid Village, XIII Koto Kampar District in 2020, totaling 1,244 consumers and based on the Slovin formula it is known that the number of samples in this study amounted to 93 respondents. The sampling technique used is accidental sampling technique. Data analysis was performed using multiple linear regression model. Based on the results of simultaneous and partial tests, the variables of product quality, price and promotion proved to have an effect on the sales volume of catfish nuggets at UPR CV. Graha Pratama Fish in Koto Mesjid Village, XIII Koto Kampar District. The close relationship that occurs between the variables of product quality, price and sales volume of catfish nuggets at UPR CV. Graha Pratama Fish in Koto Mesjid Village, XIII Koto Kampar District is very strong, while the contribution of product quality, price and sales volume variables is in a strong category.